Poetic Hells and Pacific Edens - Fulford, Tim (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractThe subject of this article is the vicious public dispute between Southey and Byron—the well-known argument that centred on the two poets’ Visions of Judgment. Precipitated by Southey’s call for censorship of immoral literature and punishment of “Satanic” authors, the dispute was won—according to twentieth-century critics—by Byron, whose devastating parody undermined the credibility of Southey’s political poetry. It has long been understood that the dispute was about more than personal enmity, that what was in question was literature’s relationship to power and its proper role in the body politic. What has received less attention is the fact that the dispute concerned not only the domestic scene (literature’s relationship to Church and State in Britain) but also the widening sphere of empire. It is my intention to focus on the imperial sphere in what follows so as to reveal that Southey and Byron were arguing in and for a new context. They were setting out rival models of colonialist and Orientalist poetry for an age in which empire was being expanded and imperialism redefined. These models include two long poems that scholars have hitherto failed to relate to the poets’ dispute—Byron’s The Island (1823) and Southey’s Tale of Paraguay (1825). Both these poems look different when we understand their place in the poets’ contest to make their own colonialist representations of native peoples prevail over the hearts and minds of the British public.